PERANCANGAN MARKAS PMI KOTA BANJARBARU - Rizky, Aulia; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The PMI Headquarters as an operational forum for martyrdom is a provider of blood transfusion health facilities in the form of a Unit Donor Darah (UDD). The blood service organized by the Indonesian Red Cross strives to provide access to services with an accessible environment for everyone. This is to support one of the Sustainable Development Goals (SDGs) on health and welfare. In the capital region of South Kalimantan, PMI Kota Banjarbaru is one of the organizations of the national association in the field of social humanitarianism that actively operates to help the community. In terms of the availability of operational containers, PMI Kota Banjarbaru does not have a headquarters as a tool for humanitarian facilities and infrastructure. This is certainly a problem for PMI Kota Banjarbaru in its duties. Access to blood services needed by the community is also hampered due to the lack of availability of blood transfusion health facilities. Therefore, this design is intended to encourage the government to build and improve the effectiveness of PMI Headquarters in the future. Through the concept of accessible building with a functional architecture approach that considers local aspects, it is hoped to produce a design for the “Markas PMI Kota Banjarbaru”, that is accessible, inclusive, and efficient, thus supporting the headquarters function in providing services.